Examining the Deciduous Tooth Eruption and Carpal Osteogenesis in Relation to Forensic age Estimation - Abdullah, Hafiza Naima Anwar, Ijaz Aziz, Amna Zafar Khan, Abdul Samad, Alia Sarfaraz, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the accuracy of deciduous teeth eruption and ossification of carpel bone of hand for estimation of forensic age. Study Design: Randomized controlled trial Place and Duration: Department of Forensic, Bacha Khan Medical college Mardan from January 2022 to June 2022. Methodology: Total 140 children of both genders with ages 5 to 15 years were enrolled in this study. All the patients were equally divided into two groups, each group consist of 70 patients. In group A dental age estimates were made using radioscopic (RVG) pictures of the left quadrant mandibular teeth by Demirjian method and the right hand wrist radiograph by Greulich and Pyle method was used for the estimation of the age of the skeleton in Group B. Statistical analysis on differences between chronological age and approximate skeletal and dental age was carried out. Results: There were 40 (57.14%) male and 30 (42.86%) females in group A and in group B 38 (54.29%) male and 32 (45.71%) females. The difference between chronological age and dental age in children with ages 5 to 10 years was 0.64±1.24 years and children with ages 11 to 15 years the difference was 0.67±0.18 years in group A and in group B difference between chronological age and skeletal age among children with age group 5 to 10 years was 0.72±1.18 years and among children with ages 11 to 15 years the difference was 0.66±1.18 years. No significant difference was observed between both groups with p-value >0.05. Conclusion: It is concluded that both procedures dental age estimation and skeletal age estimation are effective for forensic age estimation. No significant difference was observed between both methods. Keywords: Age Estimation, Forensic, Dental Age (Demirjian’s), Bone Age (Greulich and Pyle)